Interactions between acetylcholinesterase, toxic organophosphorus compounds and a short series of structurally related non-oxime reactivators: Analysis of reactivation and inhibition kinetics in vitro. (15th December 2018) - Horn, Gabriele; de Koning, Martijn Constantijn; van Grol, Marco; Thiermann, Horst; Worek, Franz
Highlights: Kinetic interactions between human AChE, organophosphates and novel non-oximes were investigated. The non-oxime 3 l, a potent reversible AChE inhibitor, protected AChE from irreversible inhibition by organophosphates. 3 l exhibited a several fold higher reactivating potency compared to ADOC. 3 l may be considered as a promising template for the development of more effective reactivators. Abstract: Poisoning by organophosphorus compounds (OP) is characterized by inhibition of the key enzyme acetylcholinesterase (AChE) and potentially fatal outcomes in humans. Insufficient efficacy of the standard therapy with atropine and AChE reactivators (oximes) against certain OP initiated synthesis of novel non-oxime reactivators basing on the common structure 4-amino-2-((diethylamino)methyl)phenol (ADOC). Recently, we reported of a pyrrolidine-bearing ADOC analogue (3 l ) with a remarkable ability to reactivate OP-inhibited AChE. This in vitro study was undertaken to determine reactivity, affinity and overall reactivation constants of3 l, the reference compound ADOC and two structural analogues with human AChE inhibited by paraoxon, sarin, cyclosarin and VX. The data showed a 10 to 34-fold reactivating potency of3 l compared to ADOC mainly due to improved affinity. Additionally, various interactions between non-oximes, human or guinea pig (GP) AChE and structurally different OP were investigated: OP-inhibited guinea pig AChE was less amenable to reactivation by ADOC and3 l than human AChE. Compound3 l was considered as potential pretreatment to prevent AChE from irreversible inhibition by OP: In the presence of 10 μM3 l inhibition of native human AChE was attenuated resulting in protective indices (PI) ranging from about 2.7 to 6.0. A combination of3 l and the bispyridinium oxime HI-6 was tested to reactivate OP-inhibited AChE: The superior reactivator of the respective OP-AChE combination dominated the reactivation process and a synergistic effect could not be observed. In conclusion, novel non-oxime reactivators like3 l may be considered as promising templates for the design of more potent therapeutics against poisoning by highly toxic OP.